PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PENGUNJUNG PADA WATERPARK KINGDOM ANIMALIA CITRALAND DI SAMARINDA - Titin Karisma (Jurnal Administrasi Bisnis Fisipol Unmul, 2021)
The purpose of this study was to determine and analyze the effect of service quality variables consisting of tangible (X1), responsiveness (X2), reliability (X3), assurance (X4), empathy (X5), both simultaneously and partially, on visitor satisfaction at Waterpark Kingdom Animalia Citraland in Samarinda, and to find out which service quality variable has the most influence on visitor satisfaction. The population in this study were visitors to Waterpark Kingdom Animalia Citraland, while the sample in this study was 100 respondents. Methods of collecting data with a questionnaire. The analysis technique used is multiple linear regression. The results of the simultaneous test (f test) show that the tangible, responsiveness, reliability, assurance, and empathy variables together have a significant effect on visitor satisfaction at Waterpark Kingdom Animalia Citraland in Samarinda. The results of the partial test (t test) show that all variables affect visitor satisfaction at the Waterpark Kingdom Animalia Citraland in Samarinda. The results of the comparison of standard regression coefficients indicate that the most influential variable is the assurance variable. Based on the analysis and discussion, it is suggested that the Waterpark Kingdom Animalia Citraland should prioritize attention on these variables, such as adding a parking lot expansion game facility, physical appearance (paint colors of statues and rides) Waterpark Kingdom Animalia Citraland Samarinda.